Synthesis and cytotoxicity of (R)‐ and (S)‐ricinoleic acid amides and their acetates. Issue 10 (3rd August 2017) - Matysiak, Sylwia; Chmiel, Agnieszka; Skolimowski, Janusz; Kula, Jozef; Pasternak, Beata; Blaszczyk, Alina
Abstract: An environment‐friendly, free of solvent, process for the synthesis of ( R )‐ and ( S )‐ricinoleic acid amides has been developed. Starting from methyl ricinoleates and pyrrolidine or ethanolamine, the corresponding amides were obtained with yields ranging from 83–88%. Among 12 synthesized derivatives of ricinoleic acid, including the starting methyl esters, amides, and their acetates, nine compounds were obtained and tested for the first time. Studies on ricinoleic acid derivatives cytotoxicity showed that methyl esters were the least cytotoxic compounds and modification of their structure resulted in increasing cytotoxicity of the obtained products against both cancer cells and normal lymphocytes. Both enantiomers of the ethanolamine‐derived amides showed the most promising anticancer potential. Abstract :